Comparative analysis of trabecular bone structure and orientation in South African hominin tali. Issue 106 (May 2017) - Su, Anne; Carlson, Kristian J.
Abstract: Tali of several hominin taxa are preserved in the fossil record and studies of the external morphology of these often show a mosaic of human-like and ape-like features. This has contributed to a growing recognition of variability characterizing locomotor kinematics of Australopithecus . In contrast, locomotor kinematics of another Plio-Pleistocene hominin, Paranthropus, are substantially less well-documented, in part, because of the paucity of postcranial fossils securely attributed to the genus. Since the talus transmits locomotor-based loads through the ankle and its internal structure is hypothesized to reflect accommodation to such loads, it is a cornerstone structure for reconstructing locomotor kinematics. Here we quantify and characterize trabecular bone morphology within tali attributed to Australopithecus africanus (StW 102, StW 363, StW 486) and Paranthropus robustus (TM 1517), making quantitative comparisons to modern humans, extant non-human apes, baboons, and a hominin talus attributed to Paranthropus boisei (KNM-ER 1464). Using high-resolution images of fossil tali (25 μm voxels), nine trabecular bone subregions of interest beneath the articular surface of the talar trochlea were segmented to quantify localized patterns in distribution and primary strut orientation. It was found that trabecular strut orientation and shape, in some cases, can discriminate amongst species characterized by different locomotor foot kinematics. Discriminant function analyses using standard trabecular bone structural properties align TM 1517 with Pan and Gorilla, while other hominin tali structurally most resemble those of baboons. In primary strut orientation, Paranthropus tali (KNM-ER 1464 and TM 1517) resemble the human condition in the anterior-medial subregion, where strut orientation appears positioned to distribute compressive loads medially and distally toward the talar head. In A. africanus tali (particularly StW 486), primary strut orientation in this region resembles that of apes. These results suggest that Paranthropus may have had a human-like medial weight shift during the last half of stance phase but Australopithecus did not.